Technical Recommendations for Penile Replantation Based on Lessons Learned from Penile Reconstruction - Roche, Nathalie A.; Vermeulen, Bob T.; Blondeel, Phillip N.; Stillaert, Filip B. (Journal of Reconstructive Microsurgery, 2012)
Penile amputation is an exceptional surgical emergency. Immediate replantation yields a high success and low complication rate. We report a case of a self-inflicted penile amputation treated with successful microsurgical replantation. Postoperative edema caused minor skin slough and temporary venous congestion was treated with medicinal leech therapy. Follow-up at 18 months showed normal subjective sensation; voiding and erectile function were present. Surgical management and technique refinements are discussed, based on a review of the literature and on our experience in penile reconstruction.
Keywords: penile replantation; microsurgery; penile reconstruction